The Establishment And Activity Of Military Judicial Commissions In The Turkestan General Governorate (Eurasian Journal of History, Geography and Economics, 2025)
This article presents information on the organization, structure, and activities of the Military Judicial Commissions operating in the Turkestan Krai, based on the audit report of the Emperor’s secret advisor, Fedor Karlovich Girs.